Economic analysis and budget impact of clostridial collagenase ointment compared with medicinal honey for treatment of pressure ulcers in the US - Mearns ES; Liang M; Limone BL; Gilligan AM; Miller JD; Schaum KD; Waycaster CR (Dove Medical Press, 2017)
Elizabeth S Mearns,1 Michael Liang,1 Brendan L Limone,1 Adrienne M Gilligan,1 Jeffrey D Miller,1 Kathleen D Schaum,2 Curtis R Waycaster2 1Truven Health Analytics, an IBM Company, Cambridge, MA, USA; 2Smith & Nephew, Inc., Fort Worth, TX, USA Objectives: Pressure ulcer (PU) treatment poses significant clinical and economic challenges to health-care systems. The aim of this study was to assess the cost-effectiveness and budget impact of enzymatic debridement with clostridial collagenase ointment (CCO) compared with autolytic debridement with medicinal honey (MH) for PU treatment from a US payer/Medicare perspective in the hospital outpatient department setting.Methods: A cost-effectiveness analysis using a Markov model was developed using a 1-week cycle length across a 1-year time horizon. The three health states were inflammation/senescence, granulation/proliferation (ie, patients achieving 100% granulation), and epithelialization. Data sources included the US Wound Registry, Medicare fee schedules, and other published clinical and cost studies about PU treatment.Results: In the base case analysis over a 1-year time horizon, CCO was the economically dominant strategy (ie, simultaneously conferring greater benefit at less cost). Patients treated with CCO experienced 22.7 quality-adjusted life weeks (QALWs) at a cost of $6,161 over 1 year, whereas MH patients experienced 21.9 QALWs at a cost of $7,149. Patients treated with CCO achieved 11.5 granulation weeks and 6.0 epithelization weeks compared with 10.6 and 4.4 weeks for MH, respectively. The number of clinic visits was 40.1 for CCO vs 43.4 for MH, and the number of debridements was 12.3 for CCO compared with 17.6 for MH. Probabilistic sensitivity analyses determined CCO dominant in 72% of 10,000 iterations and cost-effective in 91%, assuming a benchmark willingness-to-pay threshold of $50,000/quality-adjusted life year ($962/QALW). The budget impact analysis showed that for every 1% of patients shifted from MH to CCO, a cost savings of $9,883 over 1 year for a cohort of 1,000 patients was observed by the payer. Conclusion: The results of these economic analyses suggest that CCO is a cost-effective, economically dominant alternative to MH in the treatment of patients with PUs in the hospital outpatient department setting. Keywords: cost-effectiveness, budget impact, pressure ulcer, debridement, clostridial collagenase, outpatient